"Som la gent blaugrana"- FC Barcelona as ethno brand of Catalonia = "Som la gent blaugrana" - FC Barcelona jako etnomarka Katalonii - Husar, Wioletta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article takes the issue of the construction of ethno brand of Catalonia by FC Barcelona. It examines the significance of the Catalans club`s identity and mutual relationships. In addition, it shows how sport - in this case football - can become a carrier of national values, as well as being rooted in ethnicity increases the value of the club itself. Exploring the issue of Blaugrana also outlins its role in the conflict on the line Catalonia - Madrid, thus making it virtually a substitute for a political party.
Keywords: Catalonia; FC Barcelona; ethno brand; Catalan identity; Katalonia; etnomarka; tożsamość katalońska